Evaluasi Usability Aplikasi PeduliLindungi Pada Mahasiswa Kesehatan Menggunakan mHealth App Usability Questionnaire - Undari Nurkalis (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
PeduliLindungi is a mobile application to track, monitor, and stop the spread of Coronavirus Disease (COVID-19). The mHealth App Usability Questionnaire (MAUQ) was developed to assess the usability of a mobile health application. MAUQ was divided into three criteria which include ease of use, interface and satisfaction, and usefulness. Research design descriptive with a cross-sectional study approach. The population of this study was all students of the Insan Husada Surakarta Polytechnic and Jaya Jaya College of Health Sciences. The sampling technique is non-probability sampling. This study uses univariate analysis to describe the results of the application quality assessment based on user perception. The MAUQ instrument is declared valid with r-count ≥ r-table (0,1562). The correlation coefficient between the dimensions of ease of use, interface and satisfaction, and usefulness and the total score is 0.933, 0.974, and 0.935. Cronbach's Alpha values on the dimensions of convenience, interface and satisfaction, usability, and overall dimensions are 0.908, 0.950, 0.851, and 0.874 66% agreed and strongly agreed that this application was easy to use, 64.7% agreed and strongly agreed with the appearance of the application and were satisfied when using the application and 55.7% of students had a perception of very agree and agree with the usability of the app. Overall perceived ease of use, interface and satisfaction, and usefulness of the PeduliLindungi application ≥ 50%.